Transactions on Intelligent Welding Manufacturing Volume I No. 2 2017 - Chen, Shanben; Zhang, Yuming; Feng, Zhili; SpringerLink (Online service) (Singapore : Springer Nature Singapore : Imprint: Springer, 2018)
Transactions on Intelligent Welding Manufacturing (TIWM) mainly publishes selected high quality papers from the proceedings of the conference series "International Workshop on Intelligentized Welding Manufacturing (IWIWM)" and "International Conference on Robotic Welding, Intelligence and Automation (RWIA)", as well as freely contributed and peer-reviewed original research papers.
Intelligentized technologies for robotic welding -- Advanced welding robot technologies -- Programming and simulation of welding robots -- Vision guiding and tracking technologies of welding robots -- Quality control of robotic welding -- Tele-control and network technologies for robotic welding -- Sensing technologies for welding process -- Robotic welding under special environment -- Intelligentized and digital welding equipments -- Intelligentized technologies for industrial process.
Keywords: Control engineering; Robotics; Automation; Artificial intelligence; Industrial engineering; Production engineering; Control, Robotics, Automation; Artificial Intelligence; Industrial and Production Engineering; Control and Systems Theory